Student feedback on a pioneer subject on leadership and intrapersonal development in Hong Kong - Shek, Daniel T.L.; Yu, Lu; Xie, Qiu Zhi (International journal of adolescent medicine and health, 2017)
To promote leadership and intrapersonal development in university students, a subject entitled “Tomorrow’s Leaders” was developed and offered at The Hong Kong Polytechnic University. To assess the perceived effectiveness of this subject, 647 students completed the student feedback questionnaire (SFQ). Results showed that the feedback questionnaire had very good psychometric properties, including internal consistency reliability and construct validity. Regarding students’ views of the subject, results showed that students generally had good evaluation of the content of the subject, teaching quality, and perceived benefits of the subject. The present findings have implications for the teaching of general education regarding leadership development.